The Effects of Zirconia Additions on the Sintering Behaviour and Phase Stability of Hydroxyapatite Ceramics - Kutty, Muralithran G.; Singh, Ramesh (Universiti Putra Malaysia Press, 2001)
Hydroxyapatite-zirconia composites with different ratios were prepared by using the conventional ball-milling technique. Ceramic pellets prepared from these powders were compacted and sintered without distorting or cracking. The sintering behaviour (at 1250'C, 1400'C and 1600'C) of the composites were studied in terms of phase stability, densification and microstructural evolution. By X-ray diffraction, tetragonal zirconia as well as HA was identified as the major phases in the composites. In addition, small diffraction peaks corresponding to a-TCP was evident indicating sign ofHA decomposition. Reaction between the zirconia and HA to form caZro. was also detected in the composite system containing up to 20 wt% zirconia throughout the sintering regime employed. SEM examination of the sintered composites at room temperature suggested the involvement of a reactive liquid phase during sintering. The presence of zirconia phase in hydroxyapatite matrix played an important role in the stability of the HA phase.